Placing death and dying: Making place at the end of life. (December 2021) - Driessen, Annelieke; Borgstrom, Erica; Cohn, Simon
Abstract: Over the last decade, policies in both the UK and many other countries have promoted the opportunity for patients at the end of life to be able to choose where to die. Central to this is the expectation that in most instances people would prefer to die at home, where they are more likely to feel most comfortable and less medicalised. In so doing, recording the preferred place of death and reducing the number of hospital deaths have become common measures of the overall quality of end of life care. We argue that as a consequence, what constitutes a desired or appropriate place is routinely defined in a very simple and static 'geographical' way, that is linked to conceptualising death as an unambiguous and discrete event that happens at a precise moment in time in a specific location. In contrast, we draw on 18 months of ethnographic fieldwork with two inner-London palliative care teams to describe the continual work staff do to make places suitable and appropriate for the processes of dying, rather than for a singular event. In this way, instead of 'place of death' merely defined in geographic terms, the palliative care staff attend to the much more dynamic relation between a patient and their location as they approach the end of their life. Central to this is an emphasis on dying as an open-ended process, and correspondingly place as a social space that reflects, and interacts with, living persons. We propose the term 'placing work' to capture these ongoing efforts as a patient's surroundings are continually altered and adjusted over time, and as a way to acknowledge this as a significant feature of the care given. Highlights: Recording preferred place of death is a common metric of end of life care quality. What is an appropriate place is often defined in a static, 'geographical' way. Palliative care teams do 'placing work': making places suitable for dying. This work is resolutely ongoing, and a significant feature of the care given. The concept highlights the distributed nature of making place for care and dying.